Carbon Accounting: Analisis Kebutuhan dan Komponen Sistem Informasi Akuntansi berbasis Karbon - Sri Astuti; Yusron Difinubun; Musriani Musriani (Program Studi Akuntansi Unimuda Sorong, 2025)
This study aims to identify the core components required in designing a carbon accounting information system to support structured carbon emission reporting in Indonesia. Current carbon reporting systems in Indonesia are inefficient and lack transparency, necessitating the development of an integrated information system. Unlike prior studies that focus on emission reduction strategies, this study introduces a needs-based system analysis tailored to local contexts such as Papua. A descriptive qualitative approach is used, with data collected via literature studies, documentation, and observation.The system requires key components such as emission source activity data, activity volumes, emission factors, emission scopes (1, 2, and 3), and CO₂e calculation results. Identifying these components is essential in building a system that enhances carbon accountability and supports green initiatives.